Self-Reflection of Professional Performance of the Speech and Language Therapist in Education: An Approach to the Construction of the Role - Torres R., Angélica; Vega R., Yuri; Del Campo R., Manuel (Revista Chilena de Fonoaudiología, 2015)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false ES-TRAD JA X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> <!–StartFragment–> The Chilean national literature does not clearly show the role that the speech and language therapist has to accomplish in education, accepting that this area has specific characteristics which go beyond the intervention of language, communication or swallowing impairments. This study aims to establish the relation between years of professional experience as speech and language therapist in education with the standard of professional performance; and to establish the relation between such areas as special education, integration programs and preferential school subsidy with the professional performance reported by specialists working in each one of them. The study adopted a quantitative approach, with a non-experimental descriptive correlational and cross sectional design. The protocol Self-reflection of the professional practice of the speech and language therapist in education was applied to 59 speech and language therapists. The results showed that speech and language therapists stated strength in functions of identification, assessment, intervention and management. At the same time they declared less development in areas of prevention, school culture knowledge and research. There is no significant relation between the standards of performance declared by the professionals and the years of experience, or between the work area in education and professional performance. The national educational role is discussed from an international perspective. In conclusion, it is highlighted the need to initiate a self-reflection as a professional union allowing to provide feedback to the academy and to the educational area. This would also facilitate the description of the speech and language therapy practice in the educational area. <!–EndFragment–>